Persepsi Penumpang Jasa Transportasi Angkutan Umum atas Kewajaran Harga - Rufaidah, Popy (Jurnal Trikonomika, 2010)
Price fairness is one of the critical issues in managing products and services, particularly for the products which are marketed to the public. However, in the reality, price fairness could not be implemented fully if a product / a service is regulated by local governmenâs rules. This study examined the perceptions of terminal managers, drivers of the public transportation and the customers of the public transportation about price fairness (retributionâs tariff) which was implemented by local government based on Peraturan Daerah Nomor 11 Tahun 2001.